ANALISIS KUALIFIKASI DAN KOMPETENSI PEMIMPIN PADA INSTITUSI PERPUSTAKAAN DI INDONESIA - Anwar, Ahmad; Asrofi, Badrun; Ermawati, Devi; Ernawati, Ernawati (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Library in Indonesia is now facing a crisis of leadership where the leader of library is dominated by people who are not librarian. This condition is not in accordance with government regulation number 24, 2014 article 39. There are two assumption arouse regarding this issue, first is on the regulation on election of Head Library and the second one is on the librarian who doesn't have competence to be chosen as Head of Library. Seeing this phenomenon, it is important to study on what qualification and competence needed to be the head of library in Indonesia. Hopefully with this study, we will have the head of library who’s having a good qualification and competence in the field. This study employ literature methodology, which studying literature on qualification and competence of Head of Library. The result is that the qualification for head of library in province and district is at least Bachelor degree of diploma with minimum 5 years of experience in the field of library. While head of national library or university library, the minimum educational background is at least master degree with 10 years of experience in library field. For the point on competence of head of library, there are no exact regulation to regulate this from The National Library Committee. From some concept, writer proposes four basic competence which the candidate should have, which are planning, decision making, communication, and giving motivation.